Noisy information and fundamental disagreement - Philippe Andrade; Richard K. Crump; Stefano Eusepi; Emanuel Moench (Federal Reserve Bank of New York, 2013)
We study the term structure of disagreement of professional forecasters for key macroeconomic variables. We document a novel set of facts: 1) forecasters disagree at all horizons, including the very long run; 2) the shape of the term structure of disagreement differs markedly across variables: the term structure is downward-sloping for real output growth, relatively flat for CPI inflation, and upward-sloping for the federal funds rate; 3) disagreement is time varying at all horizons, including the very long run. We suggest a model with noisy information and shifting long-run beliefs that is consistent with these stylized facts. Notably, our model does not rely on the heterogeneity of prior beliefs, bounded rationality, or differences in the precision of signals across agents.
Keywords: D83; D84; E37; 330; expectations; survey forecasts; imperfect information; term structure of disagreement